2004
DOI: 10.1097/01.sla.0000109156.26378.90
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Drainage Patterns From the Breast

Abstract: In each quadrant, a breast cancer may drain to sentinel nodes in various locations. There is a distinct difference in drainage patterns between palpable and nonpalpable lesions. These findings may improve the assessment of lymphatic dissemination in invasive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
145
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(157 citation statements)
references
References 12 publications
4
145
0
5
Order By: Relevance
“…1 Surgical studies have shown that the incidence of metastatic involvement of the internal mammary nodes varies between 4% and 9% in patients with axillary node-negative breast cancer and between 16% and 65% in patients with axillary node-positive breast cancer. [2][3][4] As a consequence, surgical dissection of the internal mammary nodes was attempted but abandoned in the 1970s, since no improvement in survival was observed. 4,5 Elective irradiation of the regional nodes remained widely used until the late 1980s, when it became less popular on the basis of an overview of older trials that showed no survival benefit, despite improvement in control of locoregional disease.…”
mentioning
confidence: 99%
“…1 Surgical studies have shown that the incidence of metastatic involvement of the internal mammary nodes varies between 4% and 9% in patients with axillary node-negative breast cancer and between 16% and 65% in patients with axillary node-positive breast cancer. [2][3][4] As a consequence, surgical dissection of the internal mammary nodes was attempted but abandoned in the 1970s, since no improvement in survival was observed. 4,5 Elective irradiation of the regional nodes remained widely used until the late 1980s, when it became less popular on the basis of an overview of older trials that showed no survival benefit, despite improvement in control of locoregional disease.…”
mentioning
confidence: 99%
“…Therefore, work-up should include additional breast imaging and needle biopsy prior to operation [20]. Interpectoral nodal metastases occurring in cN0 breast cancer patients have also been confirmed by preoperative lymphoscintigraphy, but routes of interpectoral involvement has shown a distinct difference in drainage patterns between palpable and nonpalpable lesions [21]. In univariate analysis of our patients, CerbB-2 expression did not correlate with nodal involvement in Level I-II, and Rotter.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with centrally or medially located primary tumors irrespective of axillary involvement or externally located tumors with axillary involvement were randomized in a 1:1 fashion to the addition of regional nodal irradiation to the standard breast or chest wall radiation. The rationale behind the study was a reported 4-9 % involvement of the internal mammary nodes in patients with axillary node-negative breast cancer and 16-65 % in those with axillary nodepositive breast cancer [2][3][4]. The results demonstrate a small but significant benefit in disease-free survival, distant disease-free survival, and breast-related mortality.…”
mentioning
confidence: 85%